Analysis of the Implementation of the Regional Management Information System (SIMDA Next-G ) on the Quality of Bima City Government BPKAD Financial Reports - Medhitama, Deva Putri; Sasanti, Elin Erlina; Nurabiah, Nurabiah (CV. Rayyan Dwi Bharata, 2024)
This research aims to analyze the application of the Regional Management Information System (SIMDA Next-G) to the quality of Bima City BPKAD financial reports. This research uses descriptive research methods with a qualitative approach. The informants used in this research were the Head of Accounting and Reporting, Head of Budget and Operator. Data was collected through interviews and documentation. Furthermore, the data sources used are primary data and secondary data. Based on the results of the research that has been carried out, TAM is obtained, which consists of 5 primary constructs, namely 1) Perceived usefulness, 2) Perceived ease of use, 3) Attitude to wars behaviour (Attitude towards behaviour), 4 ) Behavioral intention (the perpetrator's interest), and 5) Behavior (Behavior). For perceived usefulness, the application of SIMDA-NG in inputting financial report data has been maximized because it has been able to improve performance, increase productivity, and help complete work quickly and errors rarely occur. However, records of input times are not available. Based on this research, the quality of Bima City BPKAD financial reports using SIMDA-NG already has feedback and predictive benefits, is presented on time and is complete. So, the Bima City BPKAD financial report is relevant. Regarding reliable indicators, Bima City BPKAD's financial reports have been presented honestly, verifiably and neutrally. Bima City BPKAD applies the same policies from year to year, so its financial reports can be compared. Using the new system, the quality of financial reports in the previous period with the current one can also be compared. Moreover, for indicators that can be understood, the Bima City BPKAD financial report can be understood because it is presented in a form and terms that are easy to understand.